Sorry, locals only: An experimental investigation of the affective, behavioural, and cognitive consequences of national identity denial - MAJEED, Nadyanna Binte Mohamed (Institutional Knowledge at Singapore Management University, 2022)
Existing literature shows that experiences of identity denial and questioning (IDQ) present two major consequences for racial minority groups: increased negative affect and behaviours to reassert one’s identity. The current thesis addresses two limitations in this literature—concerns about generalisability to non-US contexts, and potential consequences for cognitive functioning—by examining IDQ effects on individuals from distinct racial groups in Singapore. Through a correlational survey, Study 1 provided evidence for the incidence of IDQ in Singapore across the three racial groups, although IDQ reports were generally higher among racial minority groups (i.e., Malay and Indian) than the racial majority group (i.e., Chinese). Study 2 examined racial differences in the effects of identity denial using a quasi-experimental mixed design. Participants were randomly assigned to undergo both a denial and no denial (i.e., control) experience over two study sessions. In both sessions, their affective and reassertion responses and performance on a cognitive flexibility task were assessed as dependent outcomes. Results revealed that identity denial increased hostility and verbal reassertion similarly across racial groups. However, identity denial did not affect performance on the cognitive flexibility task. These findings suggest possible areas of further research to better understand the experiences and effects of IDQ in non-US cultural contexts.